2008
DOI: 10.1128/iai.01189-07
|View full text |Cite
|
Sign up to set email alerts
|

Host Transmission of Salmonella enterica Serovar Typhimurium Is Controlled by Virulence Factors and Indigenous Intestinal Microbiota

Abstract: Transmission is an essential stage of a pathogen's life cycle and remains poorly understood. We describe here a model in which persistently infected 129X1/SvJ mice provide a natural model of Salmonella enterica serovar Typhimurium transmission. In this model only a subset of the infected mice, termed supershedders, shed high levels (>10 8 CFU/g) of Salmonella serovar Typhimurium in their feces and, as a result, rapidly transmit infection. While most Salmonella serovar Typhimurium-infected mice show signs of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
301
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(316 citation statements)
references
References 54 publications
9
301
1
5
Order By: Relevance
“…Several studies of transmission in animal hosts have also shown a scaling of transmission fitness with pathogen load, e.g. Salmonella and Clostridium difficile transmission in mice [61,62] and Escherichia coli in cattle [63]. All these examples suggest that for some diseases and under some scenarios, infectiousness might be directly determined by pathogen load.…”
Section: Host Infectiousnessmentioning
confidence: 99%
“…Several studies of transmission in animal hosts have also shown a scaling of transmission fitness with pathogen load, e.g. Salmonella and Clostridium difficile transmission in mice [61,62] and Escherichia coli in cattle [63]. All these examples suggest that for some diseases and under some scenarios, infectiousness might be directly determined by pathogen load.…”
Section: Host Infectiousnessmentioning
confidence: 99%
“…A byproduct of oxyradical production is the generation of a new respiratory electron acceptor, tetrathionate, which enables S. Typhimurium to out-compete obligate anaerobic microbes in the gut lumen (Winter et al 2010a) by utilizing carbon sources that cannot be fermented (Thiennimitr et al 2011). The resulting bloom of S. Typhimurium in the intestinal lumen enhances its transmission to the next host by the fecaloral route (Lawley et al 2008). With the onset of adaptive immunity, the pathogen is cleared from intestinal tissues, and bacterial shedding in the feces subsides within a few weeks.…”
Section: Generalist Salmonella Serovarsmentioning
confidence: 99%
“…Large rearrangements that alter chromosomal gene order are commonly associated with a lower growth rate, because inversions may alter gene dosage, replication-transcription conflicts, or chromosome symmetry (Hill and Gray 1988;Rebollo et al 1988;Campo et al 2004). The generalist S. Typhimurium needs to multiply at a maximum growth rate in the intestine because successful transmission requires bacterial numbers in the feces to reach a sufficient threshold (Lawley et al 2008). Thus, the maximum growth rate needed for transmission might place the gene order on the chromosomes of broad-host-range Salmonella serovars under selection.…”
Section: Genomic Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of intestinal microflora with streptomycin is necessary for Salmonella-induced enteritis in mice (Barthel et al 2003) and the development of a 'super-shedder' phenotype and efficient transmission (Lawley et al 2008). Preparations of intestinal microflora are widely used in commercial broiler production and some have been confirmed to afford protection against Salmonella experimentally (Nakamura et al 2002).…”
Section: Impact Of Intestinal Microflora Onmentioning
confidence: 99%